2018
DOI: 10.35838/jrap.2018.005.02.13
|View full text |Cite
|
Sign up to set email alerts
|

Peran Penggunaan Sistem Informasi Akuntansi pada Usaha Kecil Se- Jabodetabek dengan Ketidakpastian Lingkungan sebagai Pemoderasi

Abstract: ABSTRACT This study aims to determine the role of the use of accounting information systems in Small and Medium Enterprises (SMEs) throughout Jabodetabek with environmental uncertainty as moderating. The sample in this study were 101 respondents. The results showed that the education of SME owners influenced the use of accounting information systems in SMEs as well as when moderated by environmental uncertainty, education of SME owners influenced the use of accounting information systems in SMEs. The sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…Several studies have shown that high business scale can influence MSMEs in the use of accounting information (Anggraini & Thorp, 2020;Dewi & Restika, 2018;Mustaghfiroh & Yanto, 2016;Nirwana & Purnama, 2019;Rahman & Kasdi, 2016;Santosa & Wulandari, 2019;Shirlyani et al, 2018;Susilawati et al, 2017;Whetyningtyas, 2016). Based on the theory and previous research, it can be hypothesized as follows:…”
Section: Business Scale and The Use Of Accounting Informationmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown that high business scale can influence MSMEs in the use of accounting information (Anggraini & Thorp, 2020;Dewi & Restika, 2018;Mustaghfiroh & Yanto, 2016;Nirwana & Purnama, 2019;Rahman & Kasdi, 2016;Santosa & Wulandari, 2019;Shirlyani et al, 2018;Susilawati et al, 2017;Whetyningtyas, 2016). Based on the theory and previous research, it can be hypothesized as follows:…”
Section: Business Scale and The Use Of Accounting Informationmentioning
confidence: 99%
“…High environmental uncertainty causes MSMEs with large assets and many employees to find it difficult to maintain their business conditions properly (Shirlyani et al, 2018). In a COVID-19 pandemic like this, MSMEs with more workers and larger business scales will need more accounting information to ensure their operations are running effectively and well-controlled.…”
Section: Environmental Uncertainty Moderates Business Scale On the Us...mentioning
confidence: 99%
See 3 more Smart Citations